The Effect of Conformity with Accounting Standard and Legislation Compliance to Unqualified Audit Opinion - Sarinah Joyce, Margaret Rafael; Yulinda Lenggu, Elma (Opción, 2019)
Auditors take the applicable standard and legislation as consideration in auditing processes. The unqualified audit opinion was given when the preparation of fi- nancial statements conformed. Research was conducted on East Nusa Tenggara Province Office and East Sumba District Office of Indonesia. Both of them was granted the unqualified audit opinion for two consecutive years from 2015. This achievement is impossible without the hard work of regional office of Local Rev- enue, Financial Management and Asset Agency (LRFMAA) which responsible for consolidation in the presentation of financial statements that will be audited by the State Audit Agency (SAA). Employees of LRFMAA totally 55 people who did the job is taken as a sample in this research using purposive sampling technique. Data were analysed using SPSS version 24. The results showed that conformity with accounting standards and legislation compliance had a significant positive effect on acceptance of unqualified audit opinion.